Non‐invasive prenatal testing for fetal inheritance of maternal β‐thalassaemia mutations using targeted sequencing and relative mutation dosage: a feasibility study. (9th January 2018) - Xiong, L; Barrett, AN; Hua, R; Ho, SSY; Jun, L; Chan, KCA; Mei, Z; Choolani, M
Abstract : Objective: To evaluate whether targeted sequencing and relative mutation dosage can be used to diagnose correctly inheritance of maternal β ‐thalassaemia mutations in cell‐free DNA. Design: Feasibility study using samples collected in a prenatal clinic. Setting: South East Asia. Population: Couples where both partners were known to be carriers of one of four common β ‐thalassaemia mutations or an HbE mutation, and therefore at risk of carrying a fetus affected with β ‐thalassaemia. Methods: 49 samples previously identified as having inherited a paternal β ‐thalassaemia mutation were amplified using nested polymerase chain reaction (PCR), and then sequencing. Relative mutation dosage was used to classify the fetus as having inherited the wild‐type or mutant maternal allele. Main outcome measures: Classification of the fetus as 'unaffected' (if the maternal wild‐type allele was inherited) or 'affected' with β ‐thalassaemia (if the maternal mutant allele was inherited). Results: A classification for inheritance of maternal allele was obtained in 48/49 samples (98.0%). A concordant call was made in 44/48 cases (91.7%): one false‐positive and three false‐negatives were obtained. Thus, we had an overall sensitivity of 87.5% [95% confidence interval (CI) 67.6–97.3%] and a specificity of 95.8% (95% CI 78.9–99.9%) for inheritance of maternal genotype. Conclusions: RMD for detection of inheritance of maternal β ‐thalassaemia mutations has potential for clinical use. Our sequential approach could be applied to other single‐gene disorders. Tweetable abstract: NIPT for β ‐thalassaemia achieved using nested‐PCR followed by relative mutation dosage. Tweetable abstract: NIPT for β ‐thalassaemia achieved using nested‐PCR followed by relative mutation dosage.